PENGARUH PENGETAHUAN RANTAI PASOK HALAL DAN SIKAP TERHADAP NIAT BELI MAKANAN HALAL - Prasetyo, Djoko; Qurniawati, Rina Sari; Setyawan, Andri (Perwira Journal of Economics & Business, 2025)
Recently, the halal concept has gained more attention worldwide. This is due to the increasing demand for halal food products due to the increasing number of global musicians. So far, many Muslims still feel doubtful and not confident that the food sold to the market is truly halal. Knowledge of the halal product supply chain, namely what products and how they are produced, transported and stored, will affect consumer intentions to buy. Attitudes towards halal food are very important in determining consumer behavior towards halal food. This study examines consumer knowledge of the halal supply chain and their attitudes towards the intention to buy halal food. The sample of this study was Muslim students in the cities of Salatiga and Surakarta. The results of this study prove that bringing knowledge of the halal supply chain and attitudes has an effect on the intention to buy halal food